Average chemical compositions of marine tephras including major elementsand trace elements of sediment cores during POSEIDON cruise POS513 (Table 3a) - Steffen Kutterolf; Armin Freundt; Thor H Hansteen; Rebecca Dettbarn; Fabian Hampel; Carina Sievers; Cathrin Wittig; Sharon R Allen; Timothy H Druitt; Jocelyn McPhie; Paraskevi Nomikou; Katharina Pank; et al. (PANGAEA, 2021)
Average chemical compositions of marine tephras including major elements (normalized to 100% and unnormalized) as well as trace element data and selected trace elment ratios; last column indicates # of measured shards per method. Colum 3 shows the correlations made to Aegean arc eruptions.
In: Kutterolf, S et al. (2021): Major and trace elements of Aegean Arc tephras [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938615